Academic Library Management Issues and Practices - (:unkn) unknown (My University, 2010)
This book is partially based on the contents of the course on Academic Library Management which I have been teaching at the University of Wisconsin-Milwaukee. The contents are designed to be used in connection with additional readings to be selected from the extensive lists of references at the end of each chapter as well as from other databases available to students in university and public libraries and library systems. Examples of best practices found in some academic libraries are mentioned in order to blend theory with practice.
Keywords: Library management; Academic libraries